A study on the feasibility of quantifying the population density of stored product insects in air-tight grain storage using CO2 concentration measurements. (September 2017) - Chotikasatian, Chukiat; Chayaprasert, Watcharapol; Pathaveerat, Siwalak
Abstract: This study was aimed at estimating the number of insects per 1 kg of paddy (IPK) in an air-tight mock-up silo by CO2 concentration monitoring. The first experiment was to determine the respiration rates of adult Sitophilus zeamais, Rhyzopertha dominica, and Tribolium castaneum . CO2 concentrations were recorded from groups of 50, 100 and 200 insects with and without 125 g of brown rice. The respiration rate was calculated from the slope of the CO2 concentration curve. A sample size of at least 100 insects was recommended. In 100-insect group, with the presence of food the respiration rates of S . zeamais, R . dominica, and T . castaneum were 9.57–14.13, 1.96–3.93 and 4.59–11.76 μlCO2 /insect−h, respectively. In the second experiment, S . zeamais populations at actual IPK = 2, 0.5, 0.25, 0.125 and 0.0625 in a 1.618 m 3 silo filled with paddy were quantitatively determined. Similarly, R . dominica and T . castaneum populations at actual IPK = 0.5, 0.25, 0.125 and 0.0625 in 0.064 m 3 silos were estimated in the third experiment. In each trial, small containers filled with a known number of adult insects along with brown rice were buried in the silo. Additionally, a control silo containing only disinfested paddy was set up in parallel. The insect population density was calculated from the difference in the slopes of the CO2 curves between the infested and control silos divided by the respiration rate of one insect. On average, for each species and each infestation level the estimated population density was not greater than twice of the actual ones. Although several assumptions (e.g., silos being completely sealed, only one species and one life stage of infesting insects) had to be made, monitoring CO2 concentrations could potentially be an effective tool for determining insect population density during grain storage. Highlights: The estimated population density of stored-product insect by measuring the carbon dioxide concentration was studied. The accuracy of the CO2 concentration monitoring technique was comparable to those of the existing methods. The rates of change of CO2 concentrations due to insect respiration in the trials with a food source were higher than those measured without a food source.